Education on Healthy Lifestyle for Elementary School Children Through Audio Visual Learning Media at Sanggar Bimbingan (SB) At-Tanzil Ampang Malaysia - Ade Irma Rismala; Oman Hadiana; Nanan Abdul Manan; Casnan Casnan; Tio Heri (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This study discusses the importance of healthy lifestyle education in elementary school children through audio-visual learning media at Sanggar Bimbingan (SB) At-Tanzil Ampang Malaysia. Elementary school children are very vulnerable to various diseases and health problems due to unhealthy lifestyles. Therefore, efforts are needed to educate elementary school children about healthy lifestyles so that they can grow and develop properly. This study used a qualitative approach with test data collection techniques, observation, and documentation. The results showed that the use of audio-visual learning media was very effective in providing healthy lifestyle education to elementary school children at SB At-Tanzil Ampang Malaysia. Children become easier to understand and remember the material delivered through this medium.